2011
DOI: 10.1016/j.pnpbp.2010.08.023
|View full text |Cite
|
Sign up to set email alerts
|

Fear conditioning fragments REM sleep in stress-sensitive Wistar–Kyoto, but not Wistar, rats

Abstract: Pavlovian conditioning is commonly used to investigate the mechanisms of fear learning. Because the Wistar-Kyoto (WKY) rat strain is particularly stress-sensitive, we investigated the effects of a psychological stressor on sleep in WKY compared to Wistar (WIS) rats. Male WKY and WIS rats were either fear-conditioned to tone cues or received electric foot shocks alone. In the fearconditioning procedure, animals were exposed to 10 tones (800 Hz, 90 dB, 5 sec), each coterminating with a foot shock (1.0 mA, 0.5 se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
40
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 64 publications
4
40
0
Order By: Relevance
“…Previous work has identified more proximal associations between trauma exposure, and REM sleep disturbance among humans (Habukawa et al, 2007; Mellman et al, 2002), also replicated in the current study; however, the current work demonstrates the prolonged influence that earlier-life trauma may have on the development of REM sleep physiology. This finding replicates, and thus translates to humans, similar findings previously described by experimental animal models that identified the prolonged effect that fear-conditioning has on sleep physiology (DaSilva et al, 2011; Madan et al, 2008). Furthermore, earlier-life trauma was independently associated with REM sleep fragmentation whereas later-life trauma was limited to a non-significant trend.…”
Section: Discussionsupporting
confidence: 89%
“…Previous work has identified more proximal associations between trauma exposure, and REM sleep disturbance among humans (Habukawa et al, 2007; Mellman et al, 2002), also replicated in the current study; however, the current work demonstrates the prolonged influence that earlier-life trauma may have on the development of REM sleep physiology. This finding replicates, and thus translates to humans, similar findings previously described by experimental animal models that identified the prolonged effect that fear-conditioning has on sleep physiology (DaSilva et al, 2011; Madan et al, 2008). Furthermore, earlier-life trauma was independently associated with REM sleep fragmentation whereas later-life trauma was limited to a non-significant trend.…”
Section: Discussionsupporting
confidence: 89%
“…Mellman et al have suggested that PTSD may be linked to reductions in REM following trauma and to subsequent increases over time as additional processes promote REM in ways that may assist recovery (Mellman, Kobayashi, Lavela, Wilson, and Hall Brown, 2014). Others have suggested that the lack of a strong phasic REM sleep response after a stressful event could predispose to the later increase in REM sleep phasic activity that has been observed in humans with chronic PTSD (DaSilva, Lei, Madan, Mann, Ross, Tejani-Butt, and Morrison, 2011). All of these suggestions, as well as findings from our work in animals, are consistent with REM playing a significant role in mediating stress-related emotion.…”
Section: 0 Discussionmentioning
confidence: 99%
“…Brennan, Pawlyk, Ross, & Morrison, 2005;Kumar & Jha, 2012;Sanford et al, 2003) or produces REM fragmentation (DaSilva et al, 2011;Madan et al, 2008). However, REM returns to normal following successful extinction of fear responses (Wellman et al, 2008).…”
Section: Discussionmentioning
confidence: 99%